2010
DOI: 10.1111/j.1751-7893.2010.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of subjective quality of life in first‐episode schizophrenia: perspective from Malaysia

Abstract: Different domains of self-rated quality of life correlated with different sociodemographic and clinical characteristics. Some of the characteristics were malleable and a better understanding of these could lead to improvements in the management of patients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 59 publications
3
11
0
1
Order By: Relevance
“…Both positive symptoms and general psychopathology were associated with poor overall sQoL. The association between positive symptoms and sQoL is consistent with studies conducted with chronic and FEP samples 7,12,13 that have suggested that the experience of reality distortion and other positive symptoms can have profound implications for the general subjective well-being related to life circumstances. Thus, positive symptoms, such as unusual thought content and perceptual anomalies, that occur beyond patients' control may interfere with their overall well-being.…”
Section: Discussionsupporting
confidence: 86%
“…Both positive symptoms and general psychopathology were associated with poor overall sQoL. The association between positive symptoms and sQoL is consistent with studies conducted with chronic and FEP samples 7,12,13 that have suggested that the experience of reality distortion and other positive symptoms can have profound implications for the general subjective well-being related to life circumstances. Thus, positive symptoms, such as unusual thought content and perceptual anomalies, that occur beyond patients' control may interfere with their overall well-being.…”
Section: Discussionsupporting
confidence: 86%
“…Contrary to many studies (Malla et al, 2004;Melle et al, 2005;Wegener et al, 2005;Renwick et al, 2012;MacBeth et al, 2015) which suggested a lack of association between positive symptoms and SQoL in FEP samples, our result showed that positive symptoms negatively influenced mental SQoL. Nonetheless, this finding is consistent with several first-episode studies (Chee et al, 2010;Cotton et al, 2010;Thorup et al, 2010) which examined SQoL at clinical stabilization instead of at initial presentation and revealed that positive symptoms predicted SQoL. In fact, this is in agreement with previous research which indicated that the association between positive symptoms and SQoL was stronger when patients were at clinical stabilization than during the acute phase of psychosis (Bow-Thomas et al, 1999).…”
Section: Discussionsupporting
confidence: 67%
“…Depression has consistently been found to be a robust predictor of SQoL in first-episode populations (Malla et al, 2004;Sim et al, 2004;Law et al, 2005;Melle et al, 2005Melle et al, , 2010Wegener et al, 2005;Cotton et al, 2010;Renwick et al, 2012;Gardsjord et al, 2016). Discrepant findings, however, were observed with respect to the relationships between other clinical variables and SQoL in FEP, with some studies showing premorbid adjustment (Malla et al, 2004;Melle et al, 2005;MacBeth et al, 2015), duration of untreated psychosis (DUP) (Malla et al, 2004;Melle et al, 2005;Gorna et al, 2008), positive symptoms (Gorna et al, 2008;Chee, 2010;Cotton et al, 2010), negative symptoms (Malla et al, 2004;Gorna et al, 2008;Cotton et al, 2010;Thorup et al, 2010) and func tioning (Cotton et al, 2010;Melle et al, 2010;Renwick et al, 2015) as independent factors associated with SQoL, but not others.…”
mentioning
confidence: 99%
“…The literature on QoL in multi‐episode and chronic samples suggests that QoL is greater in women than in men . However, evidence from FEP is mixed with some studies suggesting a general absence of any association between gender and QoL, whereas others support an association between better QoL and female gender …”
Section: Discussionmentioning
confidence: 99%